Different phenotypes in dermatomyositis associated with anti-MDA5 antibody: Study of 121 cases. (7th July 2020) - Allenbach, Yves; Uzunhan, Yurdagul; Toquet, Ségolène; Leroux, Gaëlle; Gallay, Laure; Marquet, Alicia; Meyer, Alain; Guillaud, Constance; Limal, Nicolas; Gagnadoux, Frédéric; Hervier, Baptiste; Borie, Raphaël; et al.
Abstract : Objectives: The predominance of extramuscular manifestations (e.g., skin rash, arthralgia, interstitial lung disease [ILD]) as well as the low frequency of muscle signs in anti–melanoma differentiation-associated gene 5 antibody–positive (anti-MDA5+) dermatomyositis caused us to question the term myositis-specific antibody for the anti-MDA5 antibody, as well as the homogeneity of the disease. Methods: To characterize the anti-MDA5+ phenotype, an unsupervised analysis was performed on anti-MDA5+ patients (n = 83/121) and compared to a group of patients with myositis without anti-MDA5 antibody (anti-MDA5−; n = 190/201) based on selected variables, collected retrospectively, without any missing data. Results: Within anti-MDA5+ patients (n = 83), 3 subgroups were identified. One group (18.1%) corresponded to patients with a rapidly progressive ILD (93.3%; p < 0.0001 across all) and a very high mortality rate. The second subgroup (55.4%) corresponded to patients with pure dermato-rheumatologic symptoms (arthralgia; 82.6%; p < 0.01) and a good prognosis. The third corresponded to patients, mainly male (72.7%; p < 0.0001), with severe skin vasculopathy, frequent signs of myositis (proximal weakness: 68.2%; p < 0.0001), and an intermediate prognosis. Raynaud phenomenon, arthralgia/arthritis, and sex permit the cluster appurtenance (83.3% correct estimation). Nevertheless, an unsupervised analysis confirmed that anti-MDA5 antibody delineates an independent group of patients (e.g., dermatomyositis skin rash, skin ulcers, calcinosis, mechanic's hands, ILD, arthralgia/arthritis, and high mortality rate) distinct from anti-MDA5− patients with myositis. Conclusion: Anti-MDA5+ patients have a systemic syndrome distinct from other patients with myositis. Three subgroups with different prognosis exist.